TALENT MANAGEMENT TO TRANSFORM THE INSTRUCTIONAL LEADERSHIP OF PRIVATE SECONDARY SCHOOL TEACHERS IN LEMBAH KLANG - Siong, Koh Aik; Abdullah, Zuraidah (EARR (Educational Administration Research and Review), 2020)
he aim of this study is to determine the level of talent management practiced by school teachers towards transforming instructional leadership in private secondary schools in Klang Valley. The quantitative research that carried out in this research focus on obtaining respondent’s view towards current study. The instrument of this study is an adaptation from the instrument done by Davies Davies (2011) on the area of talent management while the instrument of teachers’ instructional leadership PIMRS was an adaptation from a study done by Hallinger (1982). The questionnaire is modified with the adaptation of both instruments from previous studies, wich consists of six dimensions towards the aspect of talent management while seven dimensions in the aspect of instructional leadership. The realibility of current study was done upon a pilot study which show a value of 0.77 in alpha-Conbrach test, indicating that the instrument used are realiable. The result of this study was analyzed using SPSS (Statistical Packages for Social Science) Version 21.0. The study was analyzed through two descriptive analysis and inferential analysis. Descriptive analysis of this studies focuses on the measure of central value which include mean value, standard deviation and frequency of data. Apart from this, the study also employed multiple regression analysis (stepwise) to predict the dimensions that may effects talent management in school in aspect of instructional leadership among secondary school teachers in Klang Valley. The results of this study show that teachers participation in talent management in school shows a significant effect towards school’s mission and vision.